MUSLIM'S UTILITY MAXIMIZATION: an Analysis based on Maqashid Shariah - Muhammad Dayyan (Media Syari'ah, 2017)
The current analysis of utility maximization is affected by changes in income and prices. It refers to material standards which measured by numerical score representing the satisfaction that a consumer gets from a bundle of goods. Apparently, it is only to satisfy a human desire which is subjectively determined by self-interest. However, Muslim’s utility is not merely to maximize man’s satisfaction, but to achieve God pleasure as much as possible with conform his consumption to the pattern of maqashid shari’ah. This paper uses the literature review to develop a tool analysis based on maqashid shari’ah dimensions for Muslim’s utility maximization and its impact on Muslim consumption behaviors. It will address the issues of current utility concept that has been developed, the counter arguments analyse based on maqashid shari’ah within five dimensions of dharuriyah namely; preservation of faith (ad-dien), life (an-nafs), intellect (al-‘aql), progeny (an-nasl), and wealth (al-maal). Accordingly, Muslim’s maximum utility would be achieved when he spends the whole budget as closest as conform to maqashid shari’ah dimensions. Furthermore, it also objected to assist assessment of our current knowledge base, to identify misconceptions and knowledge gaps and to indicate direction for further research on the issue microeconomics especially from an Islamic perspective.